“Sanskrit palm leave manuscripts of the Library University of Jaffna –a preliminary study” - Navaneethakrishnan, S.; Visakaruban, M. (University of Sri Jayewardenepura, 2013)
Among the variety of library and archival materials, palm-leaf manuscripts are irreplaceable. They are considered as historically valuable research material. Sanskrit is an excellent and incredible treasure for a variety of subjects like science, philosophy, law, fine arts and medicine. Library of the University of Jaffna have a remarkable collection of palm leave manuscripts, particularly Palmyra palm leaves covering a wide range of subjects and written in various languages. These were kept in the archives section of this Library with limited access for scholars. Based on survey of the collection of palm-leaf manuscripts available in the Library University of Jaffna, this study was carried out to find out the subject coverage and Physical condition of Sanskrit manuscripts. It is ascertained from records that 207 palm manuscripts have been collected and two volume of catalogue of these manuscripts were published by the library in 1992 and 1997. Among the entire collection of 207 palm leaf manuscripts only two were written in Sinhalese and 22 were in Sanskrit. The balance 183 palm leaves were written in Tamil. The entire Sanskrit palm leave manuscripts were written in Granta script, which was widely used between the 6th century and the 19th century by Tamil speakers in Southern India and Sri Lanka. Further Sanskrit manuscripts have been identified under 6 subject categories namely Agama (16), Jyotisha (1), Dharmasastra (1), Ayurveda (1), Vyakarana (2) and Vedic rituals (1). Based on analysis of number of leaves, 11 were below 100 leaves, 7 were 100 to 300 and 3 were above 300 leaves. Length of the leave varies from 17.5cm to 47.5cm.Physical condition of these manuscripts were almost good (15) and 5 were slightly damaged and 2 were badly damaged. The large manuscript contains Agamic rituals in 542 leaves. This study encourages depth researches on this collection.
Keywords: Library Science; Sanskrit Language; Palm leave manuscripts; Conservation